2016
DOI: 10.1016/j.clinthera.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Signaling and the Immune Response in Sepsis: A Review

Abstract: Purpose Sepsis remains an unresolved clinical problem with high hospital mortality. Despite intensive research over decades, no treatments for sepsis have become available. Here we explore the role of adenosine triphosphate (ATP) in the pathophysiology of sepsis. ATP is not only a universal energy carrier but it also acts as an extracellular signaling molecule that regulates immune functions. ATP stimulates a large family of purinergic receptors found on the cell surface of virtually all mammalian cells. In se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 114 publications
0
27
0
3
Order By: Relevance
“…Adenosine levels rise rapidly in response to systemic inflammation to reduce pro-inflammatory/Th1-polarizing immune responses. Both ATP and adenosine bind to purinergic receptors, so the overall inflammatory effect of ATP on the biological system depends on the balance between ATP and adenosine [26]. Interestingly, levels of adenosine are significantly higher in neonatal compared to adult plasma, contributing to Th2 polarization of Toll like Receptor (TLR)-mediated responses [27,28].…”
Section: Glycolysis and The Adenosine Systemmentioning
confidence: 99%
“…Adenosine levels rise rapidly in response to systemic inflammation to reduce pro-inflammatory/Th1-polarizing immune responses. Both ATP and adenosine bind to purinergic receptors, so the overall inflammatory effect of ATP on the biological system depends on the balance between ATP and adenosine [26]. Interestingly, levels of adenosine are significantly higher in neonatal compared to adult plasma, contributing to Th2 polarization of Toll like Receptor (TLR)-mediated responses [27,28].…”
Section: Glycolysis and The Adenosine Systemmentioning
confidence: 99%
“…Indeed previous studies have shown that HTS resuscitation can reduce the injury to lungs and intestinal mucosa after hemorrhagic shock (Fernandes et al, 2009;Gao et al, 2009;Lu et al, 2010). The proposed mechanism by which HTS can mediate these effects is by shrinking cells and mechanically altering membranes, resulting in the release of ATP and promotion of T-cell function (Loomis et al, 2003;Woehrle et al, 2010;Ledderose et al, 2016). Whether a similar mechanism is involved in the effect on Tregs in our rat hemorrhagic shock model requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Они перемещаются в иммунные синапсы, где высвобождают АТФ, который при помощи P2X1-и P2X4-рецепторов активирует аутокринные пуринергические сигнальные механизмы в синаптической щели [61]. Более того, именно эти рецепторы регулируют приток ионов кальция, так как способны функционировать в качестве кальциевых каналов [60,108]. Также было показано, что АТФ ускоряет активацию Т-клеток путем усиления TCRопосредованной (от англ.…”
Section: регуляция функциональной активности клеток приобретенного имunclassified